Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.57
|View full text |Cite
|
Sign up to set email alerts
|

Learning Low-Resource End-To-End Goal-Oriented Dialog for Fast and Reliable System Deployment

Abstract: Existing end-to-end dialog systems perform less effectively when data is scarce. To obtain an acceptable success in real-life online services with only a handful of training examples, both fast adaptability and reliable performance are highly desirable for dialog systems. In this paper, we propose the Meta-Dialog System (MDS), which combines the advantages of both meta-learning approaches and human-machine collaboration. We evaluate our methods on a new extended-bAbI dataset and a transformed MultiWOZ dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…By selectively overwriting the memory module, they improved the efficiency of the dialogue state tracking task. Dai et al (2020) applied the MemN2N (Sukhbaatar et al, 2015) as task-oriented utterance encoder, memorizing the existing responses and dialogue history. Then they used model-agnostic meta-learning (MAML) (Finn et al, 2017) to train the framework to retrieve correct responses in a few-shot fashion.…”
Section: Memory Networkmentioning
confidence: 99%
“…By selectively overwriting the memory module, they improved the efficiency of the dialogue state tracking task. Dai et al (2020) applied the MemN2N (Sukhbaatar et al, 2015) as task-oriented utterance encoder, memorizing the existing responses and dialogue history. Then they used model-agnostic meta-learning (MAML) (Finn et al, 2017) to train the framework to retrieve correct responses in a few-shot fashion.…”
Section: Memory Networkmentioning
confidence: 99%
“…Huang et al (2018); Gu et al (2018); Sennrich and Zhang (2019); Bansal et al (2019); Dou et al (2019); Yan et al (2020) attempt at using meta-learning for efficient transfer of knowledge from high-resource tasks to a low-resource task. Further, some of the more recent works (Dai et al, 2020;Qian and Yu, 2019) have shown meta-learners can be used for system response generation in TOD systems which is generally downstream task for our DST task.…”
Section: Introductionmentioning
confidence: 99%
“…One of the long-standing goals of natural language processing (NLP) is to enable machines to have the ability to understand natural language and make inferences in textual data. Many applications, such as dialogue systems [1,2], recommendation systems [3][4][5], question answering [6,7], and sentiment analysis [8], aim to explore the machine ability to understand textual data. Question answering, abbreviated as QA, has emerged as an important natural language processing task because it provides a quantifiable way to evaluate an NLP system's capability on language understanding and reasoning and its commercial value for real-world applications.…”
Section: Introductionmentioning
confidence: 99%